A175 CAN HCV CORE ANTIGEN REPLACE HCV RNA TESTING IN THE ERA OF DIRECT-ACTING ANTIVIRALS?. (1st March 2018) - Almarzooqi, S; van Tilborg, M; Maan, R; Vermehren, J; Maasoumy, B; Mazzulli, T; Duarte-Rojo, A; Kowgier, M; Janssen, H L; de Knegt, R; Pawlotsky, J; Cloherty, G; et al.
Abstract: Background: Potent direct-acting antivirals (DAAs) for treatment of chronic hepatitis C virus (HCV) infection have reduced the need for on-treatment monitoring. Currently, on-treatment response and outcome are determined by HCV RNA testing. A less expensive alternative to verify viral replication is HCV core antigen (HCV Ag). Aims: The aim of this study was to determine if HCV Ag can be used for initial confirmation of viremia, on-treatment monitoring and determination of SVR in patients with chronic HCV infection receiving DAA treatment. Methods: To evaluate the role of HCV Ag in confirming SVR, patients treated with DAAs ±Peg-interferon (IFN)/RBV were included, for the purpose of assessing HCV Ag to determine relapse, patients treated with any regimen (including Peg-IFN/RBV) were included. Serum HCV RNA and HCV Ag levels were assessed at baseline (BL), on-treatment (OT), end of treatment (EOT) and week 12 and/or 24 of follow up (FU). HCV RNA was considered the gold standard. Results: In total, 181 patients were included, 112 (62%) of whom achieved SVR. Mean age was 54 years (19–79), 115 (64%) patients were male. The majority of patients was infected with genotype 1 (68%) and treated with a sofosbuvir-based regimen (58%). Median HCV RNA level at BL was 6.1 Log10 IU/mL (2.7–7.4) and HCV Ag level was 2409 fmol/L (0.85-20000). At BL, 165 out of 167 (98.8%) viremic patients tested positive for HCV Ag. Of the two patients who tested HCV Ag negative, one patient had a low RNA level (2.67 log10 IU/mL), whereas in the second patient HCV RNA level was high (6.38 log10 IU/mL). Baseline HCV Ag and HCV RNA levels were significantly correlated (R=0.87, p<0.001). At treatment week 4, HCV Ag levels had declined in all patients compared to baseline and were negative in 73%. HCV Ag at EOT was positive in 3 (2.7%) patients, all of whom achieved SVR; all were grey zone reactive (3–10 fmol/L). At week 12 FU, in one out of 68 patients (1.5%) who relapsed according to HCV RNA testing (3.11 log10 IU/mL) HCV Ag was not detected. This patient was therefore misdiagnosed as having an SVR by HCV Ag testing. Conclusions: Our data support an algorithm of testing anti-HCV antibody (Ab) positive patients with HCV Ag, reserving HCV RNA for those who are Ab positive but Ag negative. HCV Ag can be used to confirm treatment adherence but may not be adequate for confirmation of SVR, which should still be done by HCV RNA. EOT testing with either test was of little clinical benefit. Assuming current practice involves HCV RNA testing at BL, OT, EOT and SVR, use of HCV Ag could eliminate 75% of HCV RNA tests. Funding Agencies: Abbott